HOW FINANCIAL LITERACY AND LIFESTYLE SHAPE IMPULSIVE BUYING HABITS IN E-COMMERCE - Wenni Wahyuandari; Latifatul Isro'iyah; Priska Rosita Damayanti (Universitas Tulungagung, 2024)
This study examines the influence of financial literacy and lifestyle on impulsive buying behavior among e-commerce users in Tulungagung, Indonesia. Using an explanatory quantitative approach and survey data from 120 respondents, the analysis was conducted with the Partial Least Squares (PLS) method via SmartPLS software. The findings reveal that while lifestyle significantly and positively impacts impulsive buying behavior, financial literacy does not have a significant independent effect. Together, these variables explain 54.7% of the variance in impulsive buying, suggesting a moderate influence and highlighting the role of other potential factors. The results emphasize that a modest lifestyle observed among the Tulungagung community mitigates impulsive buying tendencies despite active online shopping habits, whereas financial literacy alone may be insufficient to prevent impulsive behavior, particularly among younger consumers. These insights underscore the need for integrated strategies combining financial education and behavioral interventions to promote responsible consumption, offering practical implications for policymakers, educators, and e-commerce platforms.